Water Extracts of Sapindus rarak as Medium/Reduction System for Silver Nanoparticles Formation - Yudha S., Salprima; Angasa, Eka; Mariska, Reva; Hendri, John (Asian Journal of Chemistry, 2012)
Silver ion was transformed into silver metallic form easily at room temperature using Sapindus rarak water extract. It take a few minutes to form silver nanoparticles even at room temperature. The formation of silver nanoparticles was explained in terms of the strength interaction of the silver ions with the compounds that available in the extract such as saponins, phenol and flavonoid derivatives. The UV-VIS spectrophotometry analysis shows a broad band near 400 nm as specific surface plasmon resonance of the silver nanoparticles. The TEM analysis revealed the average size of the nanopraticles under current condition was about 50 nm.